2003
DOI: 10.1242/dev.00207
|View full text |Cite
|
Sign up to set email alerts
|

Activation of theknirpslocus links patterning to morphogenesis of the second wing vein inDrosophila

Abstract: The adjacent knirps (kni) and knirps-related(knrl) genes encode functionally related zinc finger transcription factors that collaborate to initiate development of the second longitudinal wing vein (L2). kni and knrl are expressed in the third instar larval wing disc in a narrow stripe of cells just anterior to the broad central zone of cells expressing high levels of the related spaltgenes. Here, we identify a 1.4 kb cis-acting enhancer element from the kni locus that faithfully directs gene expression in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
51
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 62 publications
7
51
0
1
Order By: Relevance
“…None of the other possible activators or inhibitors of the L2 enhancer, such as sd, vg or en, showed significant alteration of their expression in ash2 I1 clones (data not shown). Moreover, using a lacZ reporter construct that includes a minimal L2 enhancer element containing only the activator and repressor sites (EX-lacZ) (Lunde et al, 2003), we observed no β-galactosidase expression in ash2 I1 homozygous discs or in mitotic clones (data not shown). Taken together, these results indicate that the ash2-induced repression of kni is independent of sal-C, and suggest that ash2 could be interacting with a kni enhancer other than L2.…”
Section: Ash2 Regulates Kni Expression Independently Of Sal-cmentioning
confidence: 91%
See 1 more Smart Citation
“…None of the other possible activators or inhibitors of the L2 enhancer, such as sd, vg or en, showed significant alteration of their expression in ash2 I1 clones (data not shown). Moreover, using a lacZ reporter construct that includes a minimal L2 enhancer element containing only the activator and repressor sites (EX-lacZ) (Lunde et al, 2003), we observed no β-galactosidase expression in ash2 I1 homozygous discs or in mitotic clones (data not shown). Taken together, these results indicate that the ash2-induced repression of kni is independent of sal-C, and suggest that ash2 could be interacting with a kni enhancer other than L2.…”
Section: Ash2 Regulates Kni Expression Independently Of Sal-cmentioning
confidence: 91%
“…The alleles bs 03267 /CyO (provided by M. Affolter), E(spl)mβ-lacZ (provided by S. Bray) and net 1 were used as intervein markers; the stock w; h kni ri-1 was used to analyse L2 development. To study the effects of ash2 on kni expression, the minimal L2-enhancer element EX-lacZ, a 1.4 kb fragment that contains an activation and repression domain of the kni gene (Lunde et al, 2003) was provided by E. Bier. For ectopic expression of sal-C, we used the UAS-sal 64d transgenic, on the first chromosome, the UAS-salr 8 transgenic, on the second chromosome, and the nubbinGal4 insertion line (provided by J. F. de Celis).…”
Section: Drosophila Strainsmentioning
confidence: 99%
“…The organization of the D-h enhancer is reminiscent of that observed in another recently described enhancer, which is necessary for the development of a specific morphological element of an adult appendage. The knirps (kni) second longitudinal wing vein (L2) enhancer drives expression of kni, which is required to initiate L2 development, in a narrow stripe within the L2 primordia (Lunde et al, 2003). As observed with D-h, localized expression of kn in the L2 primordia is established by an enhancer consisting of discrete activation and repression elements.…”
Section: Connecting Enhancer Function To Morphologymentioning
confidence: 99%
“…In response to signal X, neighboring cells outside of the sal domain express the L2 vein-organizing genes kni and knrl (Bier, 2000;Lunde et al, 1998). In addition, analysis of an L2-specific cis-regulatory element of the kni/knrl locus provided indirect evidence for negative regulation by a repressor, possibly Brk, expressed in peripheral/lateral regions of the wing disc (Lunde et al, 2003).…”
Section: Brk Plays a Role In Positioning The L2 Primordiummentioning
confidence: 99%
“…Cells expressing high levels of sal induce expression of knirps (kni) and knirps related (knrl; knirps-like -FlyBase) genes in a narrow stripe of neighboring anterior cells, which express low levels of sal (de Celis and Barrio, 2000;Lunde et al, 1998). Analysis of an L2 veinspecific enhancer element of the kni locus revealed that it consists of an activation domain containing functionally important Scalloped (Sd)-binding sites, as well as a repressor domain containing consensus binding sequences for Sal and Brk (Lunde et al, 2003). Kni/Knrl organize development of the L2 primordium by activating expression of the vein promoting gene rhomboid (rho), as well as by repressing expression of the intervein gene blistered (bs) in the vein primordial cells (Lunde et al, 1998).…”
Section: Introductionmentioning
confidence: 99%